Partisipasi Masyarakat Dalam Pendidikan Islam (Peran Komite Sekolah/Madrasah) - Siswanto Siswanto (INSANIA : Jurnal Pemikiran Alternatif Kependidikan, 2013)
Abstract: One of the development strategies of Islamic education is to empower the community as a controller of teaching and learning that is collected in a container called the School Committee or Madrasah. The committee chose the other not as an application of the autonomy of education that is being raised by the government. Among the school committee / madrasa of these are: Giving consideration (advisory agency), Support (supporting agency), controller (controlling agency) and Mediator (mediator agency). The fourth role if it can run properly, then the quality of the school / madrasah will be achieved with ease. Keywords: participation, community, school/madrasah.